SINKRETISME HINDU-ISLAM DALAM MANTRA: SEBUAH KASUS DALAM TEKS USADA MANAK - I Ketut Jirnaya (Adabiyyāt: Jurnal Bahasa dan Sastra, 2015)
The Moslem society has lived in Bali since the 14th century during the reign of Dalem Waturenggong. They have been as the minority community within the Balinese society. Among the Islamic-Balinese literary works are the Kidung of Rumaksa ing wengi, Geguritan Amad Muhammad, Geguritan Siti Badariah, and Aji Pangukiran. Another text, which is found later, is Usada Manak. This text is about Balinese traditional treatment for illness in Bali. It contains the treatment which is related to reproduction. The analysis of this text showed that this text is a result of the syncretism between Hindu and Islam in that the holy mantra of the supreme God. Om, is compiled and made parallel with the word Allah. The opening sentence of the text which expresses the request for safety, Om Awighnamastu nama siddam is made  parallel with  Bismillah irahman irahim. This syncretism showed that Moslem community is accepted by the majority of Balinese community. This indicates that  there has been a mutual understanding between Moslem and Hindu in Bali. Both share resemblances in divine philosophy with different expressions. It is functionally also believed that the God will give his blessing for all human beings and all sickness can be cured because of his blessing.